2021
DOI: 10.3390/proteomes9020030
|View full text |Cite
|
Sign up to set email alerts
|

H2B Type 1-K Accumulates in Senescent Fibroblasts with Persistent DNA Damage along with Methylated and Phosphorylated Forms of HMGA1

Abstract: Cellular senescence is a state of terminal proliferative arrest that plays key roles in aging by preventing stem cell renewal and by inducing the expression of a series of inflammatory factors including many secreted proteins with paracrine effects. The in vivo identification of senescent cells is difficult due to the absence of universal biomarkers. Chromatin modifications are key aspects of the senescence transition and may provide novel biomarkers. We used a combined protein profiling and bottom-up mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The above‐reported results indicated that in our experimental conditions the irradiated quiescent MSC cultures enter progressively into late/deep senescence. This data is in line with other findings showing that deep senescence can be reached within 20–30 days following a genotoxic injury 24–26 . Progression from early to late senescence is associated with SASP enriched in pro‐inflammatory factors.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The above‐reported results indicated that in our experimental conditions the irradiated quiescent MSC cultures enter progressively into late/deep senescence. This data is in line with other findings showing that deep senescence can be reached within 20–30 days following a genotoxic injury 24–26 . Progression from early to late senescence is associated with SASP enriched in pro‐inflammatory factors.…”
Section: Resultssupporting
confidence: 92%
“…This data is in line with other findings showing that deep senescence can be reached within 20–30 days following a genotoxic injury. 24 , 25 , 26 Progression from early to late senescence is associated with SASP enriched in pro‐inflammatory factors. De Cecco and co‐workers identified some factors (IL6, IFNA, IFNB, CCL2, MMP3) whose mRNA levels can be considered as good markers to ascertain passage to the late‐senescence stage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we did not observe significant changes in the expression of H3.3 variant genes ( H3f3a and H3f3b ) between young and aged RPE/choroid (Table S1 ). Other histone variants like H2afy2 , Hist1h2bk , and H1f0 were reported to accumulate in various aging cells and animal models (Contrepois et al., 2021 ; Kreiling et al., 2011 ; Sekeri‐Pataryas & Sourlingas, 2007 ; Zhang et al., 2005 ). Yet, our data demonstrated lower expression of these isoforms in the aged RPE (Figure 2f ).…”
Section: Discussionmentioning
confidence: 99%
“…Senescent cells, showing γ-H2AX accumulation as a result of persistent DNA damage, were found to regulate p53-dependent senescent growth arrest and senescence-associated extracellular inflammatory signaling [132,133]. Senescent fibroblast cells harbored elevated levels of the H2B type 1-K variant, but the accumulation was exclusive to cells with persistent DNA damage [134]. Thus, DNA damage-associated variant histone exchange within senescent cells likely serves to maintain the genome integrity by nucleosome deposition in damaged chromatin regions.…”
Section: Age-associated Replacement Of Canonical Isoforms By Histone ...mentioning
confidence: 99%